2016
DOI: 10.1016/j.automatica.2016.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the convergence rate of the quantum consensus: A discrete-time model

Abstract: Motivated by the recent advances in the field of quantum computing, quantum systems are modelled and analyzed as networks of decentralized quantum nodes which employ distributed quantum consensus algorithms for coordination. In the literature, both continuous and discrete time models have been proposed for analyzing these algorithms. This paper aims at optimizing the convergence rate of the discrete time quantum consensus algorithm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
(103 reference statements)
0
19
0
Order By: Relevance
“…Hence, instead of solving the Fastest Quantum Gossip problem , we solve . Formulation of the optimization problem is similar to that of the fastest discrete‐time quantum consensus problem …”
Section: Quantum Gossip Algorithmmentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, instead of solving the Fastest Quantum Gossip problem , we solve . Formulation of the optimization problem is similar to that of the fastest discrete‐time quantum consensus problem …”
Section: Quantum Gossip Algorithmmentioning
confidence: 99%
“…The second partition of interest is feasible for N ≤ d 2 and, in the work of Jafarizadeh, it has been shown that the Laplacian corresponding to this partition includes the corresponding spectrum of all other partitions. Furthermore, in the work of the aforementioned author, by generalizing the Aldous' conjecture to all partitions, it is shown that the second smallest eigenvalues of the Laplacian matrices of all partitions are equal. Therefore, for all relative values of N and d , λ 2 ( W Q , α ) and λ2false(truebold-italicW˜Q,trueα˜false) can be obtained from the Laplacian matrix corresponding to partition ( N −1,1) where its induced graph is identical to the underlying graph of the quantum network.…”
Section: Quantum Gossip Algorithmmentioning
confidence: 99%
See 3 more Smart Citations